Ueji, le précurseur du jardin japonais moderne et les hommes qui l’ont influencé - Yagasaki Zentarō (Projets de Paysage)
The purpose of this article is to shed light on the particularities of the modern Japanese garden (from the late 19th century to the early 20th century). It will mainly deal with the leisure places of the new leading class, the buildings and gardens which were aimed at receiving guests and the organisation of tea ceremonies. Our reflection shall be based on the most important patrons of Japanese gardens. Gardener Ueji, whose real name is Ogawa Jihei VII, widely participated to the development of the Japanese garden during the modern era. He started his activities at the beginning of the 20th century, and numerous documents on his works remain – the historical value of which is trying to be updated, today. Ueji mentions three men who had an essential role in his own carrier: Yamagata Aritomo, Nakai Hiromu, and Ijû.in Kanetsune. Thanks to them, Ueji succeeded in affirming his own style and became “the pioneer of the modern Japanese garden.” This article shall focus on the links that those men maintained with Ueji, and on their influence over him. It is important to take into account the cultural aspect, and in particular the world of sukisha (tea devotees) – these men of letters who were the sponsors of the modern gardens. Among all the different variations of the tea ceremony practised by these tea devotees, it is important to underline the role of the sencha culture: tea made of steeped leaves. The influence of the Chinese culture in this tradition is very strong. Thus, the theory presented in this article is that it is by trying to take hold of the typically Chinese aesthetic and vision of nature that the Japanese have created the architecture and the gardens “in the Japanese style”.